Optimalisasi Pengelolaan Media Informasi Di Organisasi Pramuka Man 2 Banyumas - Pundra Rengga Andhita; Ratna Suminar; Meyra Nanda Vianka (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: The Scout Movement is one of the major organizations in Indonesia. However, this greatness can fade if young people are not familiar with the scouting movement. This condition is currently being experienced by the Ambalan Scout Organization of Sunan Kalijaga and Dewi Masitoh Madrasah Aliyah Negeri (MAN) 2 Banyumas. Although participation is mandatory, the number of those who remain in this organization is decreasing. The scouting movement is considered less popular than others. Based on this, the Ambalan Scouts Sunan Kalijaga and Dewi Masitoh Madrasah Aliyah Negeri (MAN) 2 Banyumas collaborated with the Communication Studies Program at University of Amikom Purwokerto to optimize the management of their information media (website, social media and wall magazines) through comprehensive training with the group achievement method. A mentoring method that emphasizes efforts to build group productivity by referring to input from group members and the achievement of output targets that were prepared jointly between the Ambalan Scouts Sunan Kalijaga and Dewi Masitoh Madrasah Aliyah Negeri (MAN) 2 Banyumas and the Communication Studies Program at the University of Amikom Purwokerto. The training, which was held on February 5, 2022, was a success with more than 39 participants. The final result of this activity shows that the participants' cognitive needs regarding media management have begun to be fulfilled, the ability of participants to develop media content and distribute it appropriately, and the formation of members' commitment to maintaining the continuity of media management has begun. However, to achieve even better results, this activity requires continuous training, particularly related to aspects of media technology and media visibility strategies.Keywords: Communication; Madrasah; Media; Organization; Scout            Abstrak: Gerakan pramuka merupakan salah satu organisasi besar di Indonesia. Namun kebesaran tersebut berpotensi pudar jika anak muda mulai tidak mengenal gerakan pramuka. Kondisi inilah yang dialami Organisasi Pramuka Ambalan Sunan Kalijaga dan Dewi Masitoh Madrasah Aliyah Negeri (MAN) 2 Banyumas. Meski keikutsertaannya bersifat wajib namun diisinyalir jumlah yang bertahan di organisasi ini semakin menurun. Gerakan pramuka dinilai kalah populer dibandingkan lainnya. Salah satu penyebabnya adalah belum optimalnya pengelolaan media informasi. Berdasarkan hal tersebut, Pramuka Ambalan Sunan Kalijaga dan Dewi Masitoh MAN 2 Banyumas menggandeng Program Studi Ilmu Komunikasi Universitas Amikom Purwokerto untuk melakukan optimalisasi pengelolaan media inofrmasinya (website, media sosial dan mading) melalui pelatihan komprehensif dengan metode group achievement. Sebuah metode pendampingan yang menekankan upaya membangun produktivitas kelompok dengan mengacu pada input dari anggota kelompok dan pencapaian target output yang disusun bersama antara mitra dan anggota kelompok. Pelatihan yang diadakan tanggal 5 Februari 2022 ini berjalan sukses dengan diikuti oleh lebih dari 39 peserta. Hasil akhir kegiatan ini memperlihatkan mulai terpenuhinya kebutuhan kognisi peserta mengenai pengelolaan media, terbentuknya kemampuan peserta dalam menyusun konten media serta mendistribusikannya dengan tepat, dan terbentuknya komitmen anggota untuk menjaga kontinuitas pengelolaan medianya.Kata Kunci: Komunikasi; Madrasah; Media; Organisasi; Pramuka